Edukasi gizi seimbang: Gerakan cegah stunting (GEGATI) - Apdola, Zikrina; Anggraini, Anggraini; Rachmawati, Fijri; Fratama, Aldy; Putri, Miranda (JOURNAL of Public Health Concerns, 2025)
Background: Stunting is the stunted growth and development of children due to chronic malnutrition. This is characterized by a child's height not meeting standards, especially during the first 1,000 days of life. In Banjar Masin Village, several children fall into the malnourished category. Purpose: To provide knowledge to expectant mothers and mothers with toddlers regarding stunting, its management and prevention, and the importance of balanced nutrition for child growth and development. Method: The GEGATI "Stunting Prevention Movement" outreach program was held at the Banjar Masin Village Hall, West Kota Agung District, on August 14, 2025. The event was held from 10:00 AM to 12:00 PM WIB. Forty-four participants, including pregnant women and mothers with toddlers, attended the event. The outreach program was conducted interactively, with open discussions and questions and answers. The informational materials covered stunting prevention in the health sciences, including using turmeric and honey, and processing tempeh into nuggets. Pre-test and post-test were used to measure changes in respondents' knowledge levels. Results: The majority of respondents' knowledge before (pre-test) education was in the poor category (39%, 88.6%), while the majority of respondents' knowledge after (post-test) education was in the good category (35%, 79.6%). Conclusion: Counseling activities are very effective in improving and increasing the understanding of stunting among expectant mothers and mothers with toddlers. Increased knowledge about nutrition and health can shape the mindset and parenting practices of the community to improve stunting prevention. Suggestion: Village cadres are expected to coordinate with the village government and health workers and regularly organize community knowledge-building activities related to nutrition, healthy lifestyles, and environmental protection. This will specifically empower mothers and expectant mothers to gain knowledge about childcare, from pregnancy through the first 1,000 days of life. Keywords: Balanced nutrition; Prevention; Stunting Pendahuluan: Stunting adalah terhambatnya tumbuh kembang anak karena kekurangan gizi kronis. Hal ini bisa ditandai dengan tinggi badan anak yang tidak sesuai standar, terutama pada 1000 hari pertama kehidupan. Di Pekon Banjar Masin, ada beberapa anak yang masuk dalam kategori gizi buruk. Tujuan: Untuk memberikan pengetahuan calon ibu dan ibu yang mempunyai balita terkait stunting, penanggulangan dan pencegahannya, serta gizi seimbang yang sangat penting untuk tumbuh kembang anak. Metode: Penyuluhan GEGATI “Gerakan Cegah Stunting” di Balai Pekon Banjar Masin, Kecamatan Kota Agung Barat dilaksanakan pada tanggal 14 Agustus 2025. Kegiatan ini dilaksanakan pada pukul 10.00-12.00 WIB. Responden yang hadir dalam acara ini sebanyak 44 peserta yang terdiri dari ibu hamil dan ibu yang mempunyai balita. Penyuluhan ini dilakukan secara interaktif, diskusi terbuka dan tanya jawab bersama dengan para responden. Materi informasi terkait dengan pencegahan stunting dalam bidang ilmu kesehatan, dengan temulawak dan madu serta dengan olahan tempe menjadi nugget. Pre-test dan post-test digunakan untuk mengukur perubahan tingkat pengetahuan responden. Hasil: Menunjukkan bahwa tingkat pengetahuan responden sebelum (pre-test) pemberian edukasi adalah sebagian besar dalam kategori kurang yaitu sebanyak 39 (88.6%), sedangkan tingkat pengetahuan responden sesudah (post-test) pemberian edukasi adalah sebagian besar dalam kategori baik yaitu sebanyak 35 (79.6%). Simpulan: Kegiatan penyuluhan sangat efektif memberikan peningkatan dan pemahaman calon ibu dan ibu dengan balita terhadap stunting. Meningkatnya pengetahuan tentang gizi dan kesehatan dapat membentuk pola pikir dan pola asuh masyarakat menjadi lebih baik dalam pencegahan terjadinya stunting. Saran: Diharapkan para kader desa untuk selalu berkoordinasi dengan pemerintah desa dan tenaga kesehatan, secara berkala menyelenggarakan kegiatan peningkatan pengetahuan masyarakat terkait pemahaman tentang gizi, pola hidup sehat dan menjaga lingkungan, sehingga secara khusus untuk para ibu atau calon ibu mendapatkan pengetahuan tentang pola asuh anak, baik sejak kehamilan sampai 1000 hari pertama kehidupan.